2008
DOI: 10.1111/j.1440-1843.2008.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐sensitivity C‐reactive protein: A predicative marker in severe asthma

Abstract: These findings suggest that hs-CRP might be a sensitive marker for severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 31 publications
(39 reference statements)
6
33
2
Order By: Relevance
“…Also, serum hs-CRP showed significant positive correlation with asthma severity and significant negative correlation with ACT and FEV 1 % of predicted in all studied asthmatic patients. These results are in accordance with Takemura et al [13], Kilic et al [14] and Qian et al [15] who explained that inflammatory process differs with staging of asthma after the exclusion of the role of infection. The severity of the disease significantly relies on the volume of the bronchial inflammation and the amount of inflammatory mediators released in circulation and hence the acute phase reactant will be synthesized by the liver, CRP is one of the most important acute phase reactants.…”
Section: Discussionsupporting
confidence: 92%
“…Also, serum hs-CRP showed significant positive correlation with asthma severity and significant negative correlation with ACT and FEV 1 % of predicted in all studied asthmatic patients. These results are in accordance with Takemura et al [13], Kilic et al [14] and Qian et al [15] who explained that inflammatory process differs with staging of asthma after the exclusion of the role of infection. The severity of the disease significantly relies on the volume of the bronchial inflammation and the amount of inflammatory mediators released in circulation and hence the acute phase reactant will be synthesized by the liver, CRP is one of the most important acute phase reactants.…”
Section: Discussionsupporting
confidence: 92%
“…Mild persistent asthma was also the commonest form of asthma severity in children at 1 year follow up in Beninas reported by Oviawe et al 18 . This pattern was not in conformity with the findings of Qianet al 19 where severe persistent asthmatic subjects constituted the largest group with 37.0%, followed by mild intermittent with 29.9%, moderate persistent were 22.4% and mild persistent 10.7%. Reason for this difference may be due to a larger sample size used by Qianet al 19 where 281 asthmatic subjects were studied.…”
Section: Discussioncontrasting
confidence: 86%
“…This pattern was not in conformity with the findings of Qianet al 19 where severe persistent asthmatic subjects constituted the largest group with 37.0%, followed by mild intermittent with 29.9%, moderate persistent were 22.4% and mild persistent 10.7%. Reason for this difference may be due to a larger sample size used by Qianet al 19 where 281 asthmatic subjects were studied. Another explanation for the difference may be probably because developed countries have high level of industrialization with attendant dusty air and air pollutants which may contribute to severe persistent asthma seen in such countries.…”
Section: Discussioncontrasting
confidence: 86%
“…Moreover, in a small recently published prospective cross-sectional study in patients with mild asthma it was reported that sputum IL-6 levels correlated inversely with postbronchodilator FEV 1 6. IL-6 is responsible for the modulation of synthesis of acute phase proteins such as C-reactive protein, whose serum level is increased in severe asthma 7. IL-6 induces its inflammatory activity by interacting with its receptor and a signal transducing non-ligand (gp130), but also via the soluble IL-6 receptor (sIL-6R) 8.…”
mentioning
confidence: 99%